School geography: the use of tactile teaching materials for education and guidance of people with visual impairment - Medeiros, Monica Leticia de; Araújo, Samara dos Santos de; Sobrinho, Djanni Martinho dos Santos (Revista Ensino de Geografia (Recife), 2024)
Geography contributes to the understanding of spaces, being essential for the individual's citizenship formation. Recognizing this importance, it is necessary to consider the aspects that permeate the educational sphere, an approach that originates the investigation of this article, which seeks to understand how inclusive practices from the perspective of School Geography, based on didactic-pedagogical resources, can facilitate the process of teaching and learning for students with visual impairments or low vision, with emphasis on the production and manipulation of tactile teaching materials. To achieve this, a bibliographical survey of authors who discuss school geography, inclusion and teaching practices became essential. In addition, documentary research was used on documents that are part of Brazilian educational legislation, such as the National Common Curricular Base (BNCC). The present investigation is part of the results of the productions developed in the Geography Teaching curricular component in the pedagogy course of a Higher Education institution in Rio Grande do Norte, at which time the undergraduates produced tactile materials based on themes related to population studies . From the readings, document analysis and production of the material, we consider the tactile teaching resource as a creative and didactic tool, which enables the students' learning process.